PENERAPAN KONSEP SUSTAINABLE FINANCE: Model Analitycal Hierarchy Process - Setiyowati, Harlis; Trisnawati, Luh Putu Puji (JURNAL LENTERA AKUNTANSI, 2023)
The idea of sustainable finance has gained acceptance on a global and regional scale, including in Indonesia. Applications of this new financial idea face challenges. Making a model for sustainable finance implementation is the aim of this study. The AHP model's goal is to establish a economic, social, and value  environment and corporate governance. The first level is a factor, namely obstacles to the implementation of sustainable finance, namely; economic, social and environmental aspects, issues of rules and regulations, disclosure of sustainable reports and technological interventions. Based on the results of testing the AHP model, the most important factor in implementing the concept of Sustainable Finance is the "Economic, Social and Environmental Aspects" factor with a weight of 0.390, the second most important factor is "Rules and Regulation Issues" with a weight of 0.319, then the "Disclosure of Sustainability Reports" factor with weight 0.158 and the lowest is the "Technological Intervention" factor with a weight of 0.132. Meanwhile, based on the test results, the most important actor in the concept of Sustainable  Finance based on test results, namely Financial Services Institutions with a weight of 0.338. The second most important actor is the Issuer with a weight of 0.275. The third most important actor is a Public Company with a weight of 0.264, and the actor with the lowest weight is All Related Parties with a weight of 0.147.  Recommend that For financial institutions and investors to be prepared to participate in ESG-based businesses, legislation and norms pertaining to sustainable finance urgently need to be improved, particularly fines for non-compliance and purposeful manipulation of sustainability reports.Keywords: AHP, Sustainable Finance